PENGARUH LITERASI EKONOMI SISWA, HASIL BELAJAR EKONOMI, DAN TEMAN SEBAYA TERHADAP PERILAKU KONSUMSI SISWA SMP NEGERI DI SURABAYA BARAT - Murniatiningsih, Endah (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
This study aimed to analyze the effect of the Students Economic Literacy, the results of the economic study, and peers on consumption behavior of students of SMP Negeri Surabaya Western Conference. The research population was students of SMP Negeri 28 Surabaya class VIII as many as 369 people and students of SMP Negeri 40 Surabaya class VIII as many as 330 students, with a total sample of 254 students. The data collection techniques using questionnaires and documentation. Methods of analysis using multiple linear regression techniques. The results showed that the students economic literacy, the results of the economic study, and peer partially has a positive and significant effect on consumption behavior. The students economic literacy of students, the results of the economic study, and peer simultaneously positive significant effect on consumption behavior of students